Pré-fabricados lingüísticos: estrutura e funcionamento de sintagmas verbais idiomatizados - por uma abordagem cognitivo-funcional em sala de aula - Costa, José da Luz (2007)
This work aims at under the cognitive-functional perspective describing, inside the vast domain of the linguistic prefabs, the structure and the functioning of the Idiomatic Verb Phrases (SVIs), produced by speakers of the Portuguese from Brazil, located in Natal (RN). From the functionalist presupposition that the language is used essentially to assist to communicative demands, it is observed that its morphologic-syntactic structure is conditioned to the inherent pragmatic vicissitudes to the verbal interaction of subjects, socially heterogeneous and historically established. It is focalized, in the composition of SVIs, the relationships VT + OD (transitive verb + direct object), characterizing the syntactic-semantic nature of the verb and of the respective verbal complement. Those verb combinations + complement can be interpreted as lexical structures, reflexes of the idiomaticity inherent to conventional constructions already systematized in the users' of the language cultural repertoire. It is sought, still, to glimpse the cognitive and discursive motivations pertinent to that linguistic phenomenon. In the investigative process, are analyzed exclusive data of speech collected in Corpus Discurso & Gramática a lingua falada e escrita na cidade do Natal, organized by Furtado da Cunha (1998). The adopted methodological procedures configure as methods of empiric analysis and use of the intuition, being emphasized the qualitative approach (explanatory) of the data with quantitative support of statistical indicators. It shows, finally, a grating of didactic suggestions on SVIs, for Portuguese's classes, as subsidies to the educational practice in the Medium Teaching and in the course of Letters.